Stress Drought and Mycorrhizal Dose on the Growth Characteristics of Boci Sawala Pandanga Morotai Local Peanuts - Kisey Bina Habeahan; Sofyan Samad; Rima Melati (Jurnal Penelitian Pendidikan IPA, 2023)
Mycorrhizal can provide plant resistance when drought came. Thus, this study aims to examine the effect of stress drought and mycorrhizal dose on the growth of Boci Sawala Pandanga Morotai local peanuts. The study was conducted at the BPTP screen house North Maluku in Kusu Village, Tidore Kepulauan City, North Maluku Province from March to June 2022 with the elevation of 50m above sea level. It utilized a factorial design with 2 factors. The first factor is the drought (K) 2 levels (K0 = optimal and K1 = stress), and the second factor is mycorrhizal (M) 4 levels (M0 = 0 g/polybag, M1 = 20 g/polybag, M2 = 25 g/polybag, M3 = 30 g/polybag) with 3 replications. The parameters observed consisted of relative growth rate, flowering age, and number of gynophores. The fingerprint results showed that the Boci Swala Pandanga Morotai local peanuts cultivar is tolerant to drought conditions which can be seen from the relative growth rate, number of ginophores, and the fastest flower. With drought stress conditions by giving mycorrhiza 30 g/polybag of peanuts land, it still grew and worked.